Combinatorial Libraries of Stilbene Fused Chalcone and Flavanone Derivatives: Synthesis and Anti-Proliferative Properties - Akçok, İsmail; Çağır, Ali (Izmir Institute of Technology, 2009)
Flavonoids and stilbenes have attracted great attention as potential pharmaceuticals. Up to date more than 5000 natural flavonoid derivatives have been isolated from natural resources. Flavonoids are most commonly known for their antioxidant activity. Additionally they might show various biological activities such as antibacterial, antiviral, anti-fungal, topoisomerase I and telomerase inhibitors, antiangiogenesis etc. Stilbenes are another class of compounds, which are also isolated from natural sources having anti-cancer, anti-inflammatory, blood sugar lowering and beneficial cardiovascular activities.In this study, synthesis of stilbene fused chalcone and stilbene fused flavanone systems were aimed. By means of that, it might be possible to produce a compound which can be used for at least two different biological activity or they might show a single activity with a great enhancement.For this purpose, a series of chalcone, flavanone, stilbene, stilbene fused chalcone, and stilbene fused flavanone derivatives were synthesized. Synthesis of stilbene fused chalcones and stilbene fused flavanones were accomplished by two different pathways. Two small combinatorial libraries of stilbene fused chalcones and stilbene fused flavanones have been built starting from four different acetophenones and four different styrenes. Preliminary anti-tumor activities of selected examples against human mammary adenocarcinoma cells (MCF-7) and human prostate cancer cell lines (PC3) were also evaluated.
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2009
Includes bibliographical references (leaves: 77-81)
Text in English; Abstract: Turkish and English
xvi, 94 leaves
Keywords: QD441 .A31 2009; Flavonoids; Stilbene--Derivatives